Previously unaccounted atmospheric mercury deposition in a midlatitude deciduous forest - Obrist, Daniel (Proc Natl Acad Sci U S A, 2021)
Mercury is toxic to wildlife and humans, and forests are thought to be a globally important sink for gaseous elemental mercury (GEM) deposition from the atmosphere. Yet there are currently no annual GEM deposition measurements over rural forests. Here we present measurements of ecosystem–atmosphere GEM exchange using tower-based micrometeorological methods in a midlatitude hardwood forest. We measured an annual GEM deposition of 25.1 µg ⋅ m(−2) (95% CI: 23.2 to 26.7 1 µg ⋅ m(−2)), which is five times larger than wet deposition of mercury from the atmosphere. Our observed annual GEM deposition accounts for 76% of total atmospheric mercury deposition and also is three times greater than litterfall mercury deposition, which has previously been used as a proxy measure for GEM deposition in forests. Plant GEM uptake is the dominant driver for ecosystem GEM deposition based on seasonal and diel dynamics that show the forest GEM sink to be largest during active vegetation growing periods and middays, analogous to photosynthetic carbon dioxide assimilation. Soils and litter on the forest floor are additional GEM sinks throughout the year. Our study suggests that mercury loading to this forest was underestimated by a factor of about two and that global forests may constitute a much larger global GEM sink than currently proposed. The larger than anticipated forest GEM sink may explain the high mercury loads observed in soils across rural forests, which impair water quality and aquatic biota via watershed Hg export.